Public attitudes and the socio-political divide surrounding onshore wind power in Norway - Kraft, Pål; Kraft, Brage (Frontiers in Sustainable Energy Policy, 2025)
IntroductionNorway's goal to significantly increase onshore wind power production requires building public trust and addressing societal concerns.ObjectiveThis study investigated Norwegian attitudes toward onshore wind power at national and local levels, examining the influence of socioeconomic factors, the “Anywhere-Somewhere” worldview, climate change denial, and materialism.MethodsA representative survey of 1,029 Norwegian adults (aged 18 years and above) was conducted.ResultsPublic opinion on national onshore wind power development was almost evenly divided, although negative attitudes tended to be more extreme. However, local opposition was significantly higher (60%), primarily because of concerns about environmental impacts (harm to wildlife, visual impacts, noise, and land use). Socioeconomic factors did not predict attitudes, but opposition strongly correlated with a “Somewhere” worldview; this relationship was not mediated by climate change denial or materialism.ConclusionSignificant public opposition to onshore wind power exists in Norway, particularly within marginalized sociocultural groups.ImplicationsAchieving Norway's renewable energy targets requires inclusive policies that address citizen concerns.